2014
DOI: 10.5005/jp-journals-10030-1088
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Maxillofacial Fractures in Road Traffic Crashes in an Indian Rural Tertiary Center

Abstract: Background and objectives: Road traffic crashes are reported to be the leading cause of maxillofacial fractures in developing countries. The large variability in reported incidence and etiology is due to a variety of contributing factors, including environmental, cultural and socioeconomic factors. The study aims at describing the patterns of maxillofacial fractures in road traffic crashes by clinical and radiological methods and to study the complications associated with these fractures. Materials and methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
4
1
1
Order By: Relevance
“…The incidence of facial bone fractures in this study was 89.7%, which was higher than what has been reported in other studies elsewhere 1,3,22 but slightly lower than what was reported in Nigeria. 14 In this study, the mandible was the commonest bone fractured either in isolation or in combination with other bones, while the frontal bone was the least affected.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…The incidence of facial bone fractures in this study was 89.7%, which was higher than what has been reported in other studies elsewhere 1,3,22 but slightly lower than what was reported in Nigeria. 14 In this study, the mandible was the commonest bone fractured either in isolation or in combination with other bones, while the frontal bone was the least affected.…”
Section: Discussioncontrasting
confidence: 78%
“…Majority of the victims of motorcycle crashes were young individuals with a mean age of 29 years which was almost comparable to other means which have been reported in several studies elsewhere. 1,3,13,14,18 The pride of riding motorcycles and competition for passengers sometimes compel the young motorcyclists to ride in competitive speeds that expose them to risks of crashing amidst the busy traffic jams. During this study, a typical profile of a motorcycle casualty in Tanzania was a male rider 20-39 years old, findings which were contrary to those in a report from Malaysia where the crash victims were younger (16-25 years).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The age group between 21 and 30 years was more affected compared to the other age groups that were in concordance with other studies conducted by Melmed,[ 14 ] Rowe NL,[ 15 ] and Timoney. [ 16 17 ] The younger age group was more affected due to the active energetic life style, more outdoor activities, and probably as they are more involved in reckless driving without the use of safety measures such as helmets. The number of fractures encountered in children is significantly less as the bones are highly elastic with a reduced volume of the PNS.…”
Section: Discussionmentioning
confidence: 99%
“…Кількість травмованих осіб підвищилася до 21957 осіб (на 5,8%) у порівнянні із попереднім звітним періодом, в межах якого кількість таких осіб складала 20759. Фактичне зростання кількості травмованих осіб було зареєстроване в більшості областей України, окрім Вінницької, Волинської, Дніпропетровської, Київської, Кіровоградської, Львівської, Полтавської, Тернопільської та Черкаської [10,11]. Значну складову у структурі травм, що виникають в результаті ДТП займають травми щелепно-лицевої ділянки, які реєструються більш, ніж в половині випадків дорожньо-транспортних пригод.…”
Section: вступunclassified